Analisis Perkembangan Kota Bukittinggi dan Sekitarnya Tahun 2005-2022 Menggunakan Metode Spatial Metric - Warni, Annisa Nolvi; Ahyuni, Ahyuni (Lembaga Yasin AlSys, 2024)
The aim of this research is to: 1) Understand the physical development of Bukittinggi City and its surroundings in the period 2005-2015 and 2022, 2) Understand the spatial pattern of development of Bukittinggi City and its surroundings. This type of research is quantitative, using secondary data, namely SPOT images for the period 2005, 2015 and 2022. The analysis technique used is manual digitization to produce maps of built-up areas and metric spatial analysis to determine city development patterns using 5 methods, namely: PD , NP, LPI, LSI, and MPS. The overlay method is used to obtain patterns of development of built-up land regarding slopes, roads, distribution of facilities and population development. This research found: The physical development of the City of Bukittinggi and its surroundings in the period 2005-2022 shows a lot of development and improvement, which can be seen by the shrinking of non-built-up areas in each time period tending towards Urban Sprawl marked by an increase in built-up areas which spread towards the outskirts of the city. due to population growth. The development of built-up areas in the city of Bukittinggi and its surroundings tends to grow in areas with flat and gentle slopes and tends to gather on main and central roads, so it can be concluded that the development of the city of Bukittinggi and its surroundings is still concentric.